The influence of bowel management on urodynamic findings in spina bifida children with detrusor overactivity and detrusor sphincter dyssynergia. Issue 5 (October 2020) - Milivojevic, Sasa; Milic, Natasa; Lazovic, Jelena Milin; Radojicic, Zoran
Summary: Objective: To examine the effects of bowel management on urodynamic findings in spina bifida children with detrusor overactivity (DO) and detrusor sphincter dyssynergia (DSD). Material and methods: Between 2014 and 2019 we prospectively evaluated 39 consecutive spina bifida children with DO and DSD (18 (46.2%) boys and 21 (53.8%) girls, aged 4–16 years; mean age 9.5 ± 3.7 years) who received bowel management and we treated their bowel dysfunction with an aim of alleviating the symptoms of constipation, preventing constant overdistension of the rectosigmoid, providing regular emptying of the colon and faecal continence. Bowel management included daily enema, laxative application and a special diet who was performed during 12 months. All children had undergone urodynamic studies before and after starting bowel management, with no changes in their urological treatment. Results: Bowel management caused an increase in maximum bladder capacity from 183.0 (112.0–234.0) to 237.0 (165.0–298.0) (p < 0.001). When maximal bladder capacity adjusted for age there was also significant increment (adjusted before 0.54 (0.47–0.64), adjusted after 0.75 (0.70–0.82), p < 0.001). In addition, we observed a decrease in maximal detrusor pressure from 64.3 (49.0–77.0) to 46.4 (32.0–59.0) cm H2O (p < 0.001) and an increase in bladder compliance from 3.0 (2.0–3.3) to 5.6 (3.9–6.6) ml/cm H2O (p < 0.001). There was also significant reductions in leak point pressure from 62.0 (48.0–69.0) to 39.0 (30.0–43.0) cm H2O (p = 0.001), and significant reductions in post-void residual volume (PVR) from 165.0 (128.0–187.0) to 98.0 (68.0–136.0) ml in our 13 patients who could achieve spontaneous voiding (p = 0.001). Conclusion: Administering bowel management may be useful for bladder function and urodynamic findings in spina bifida children with DO and DSD. Therefore, bowel management should form an integral part of the treatment in spina bifida children with DO and DSD. Image 1